Representasi Lokatmala dalam Penciptaan Tari Bising dalam Hening - N. Wina Resky Agustina (Pascasarjana ISBI Bandung, 2020)
Bising Dalam Hening (Noise in Silence) is a dance work inspired by the atmosphere of Cianjuran song’s mamaos entitled “Lokatmala”. This atmosphere inspires the soul about, a longing for the cool, peaceful, and peaceful rural atmosphere. The poetry of the song then became an expression of contemporary dance works, which later developed into a phenomenon of natural destruction due to human activity. The theory applied in the creative process of creating this dance is the hermeneutic theory by Paul Ricoeur. This is as an interpretation of understanding in explaining, translating, and expressing ideas about natural beauty. The methods used include exploration, improvisation and formation stages. Through the theory and method used, coupled with the creative process of realizing ideas of religious experience about self-memory, this dance work can be realized. The admiration of the divine work reminds us how nature has become a part of human life, which must be maintained as an extension of God’s hand. Furthermore, It becomes a form of dance that has a moral message about the relationship between humans and nature and its Creator.Keywords: Dance, silent noise, natural environment, hermeneutics.